The clinical application of tumor markers in the screening of malignancies and interstitial lung disease of dermatomyositis/polymyositis patients: A retrospective study. (13th June 2018) - Lim, Chong Hong; Tseng, Chih-Wei; Lin, Ching-Tsai; Huang, Wen-Nan; Chen, Yi-Hsing; Chen, Yi-Ming; Chen, Der-Yuan
Objective: To examine the clinical utility of tumor markers in dermatomyositis/polymyositis patients in Taiwan. Method: Data were collected retrospectively from the database of Taichung Veterans General Hospital in Taiwan from 1998 to 2014. Patients who fulfilled Bohan and Peter criteria of dermatomyositis/polymyositis were recruited. Serum level of tumor markers including carcinoembryonic antigen, alpha-fetoprotein, carbohydrate antigen 125, carbohydrate antigen 19-9 and carbohydrate antigen 15-3 were measured. The occurrence of malignancies and interstitial lung disease was identified. The association of tumor markers with malignancies and interstitial lung disease was examined using Chi-square test or Fisher's exact test. Results: Among the enrolled 151 patients, 98 (64.9%) dermatomyositis and 53 (35.1%) polymyositis, a total of 15 malignancies were detected: breast ductal carcinoma (n = 4), bladder transitional cell carcinoma (n = 2), lung adenocarcinoma (n = 2), cervical intraepithelial neoplasia 3 and papillary squamous cell carcinoma (n = 2), colorectal (colon and rectal adenocarcinoma) (n = 2), uterine adenocarcinoma (n = 1), nasopharyngeal carcinoma (n = 1) and hematological malignancy (myelodysplastic with excess blast cells) (n = 1). Among the patients with malignancies, 13 (86.7%) had dermatomyositis, 2 (13.3%) polymyositis and 3 (20%) interstitial lung disease. The mean duration from dermatomyositis/polymyositis diagnosis to the occurrence of malignancies was 6.05 ± 5.69 years. There was no significant association of raised tumor markers with the occurrence of malignancies (p > 0.085), while a significant association was observed between the elevated levels of carbohydrate antigen 15-3 and the presence of interstitial lung disease (p = 0.006). Conclusion: Tumor markers were not useful in malignancy screening or dermatomyositis/polymyositis patients in this tertiary center. The evaluation of the occurrence of malignancy in dermatomyositis/polymyositis patient should include a multidimensional approach. A raised level of carbohydrate antigen 15-3 may be a potential indicator of the presence of interstitial lung disease in dermatomyositis/polymyositis patients.